Multilayer MoS2 transistors enabled by a facile dry-transfer technique and thermal annealing - Yang, Rui; Zheng, Xuqian; Wang, Zenghui; Miller, Christopher J.; Feng, Philip X.-L. (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2014)
Molybdenum disulfide (MoS2) two-dimensional nanostructures have been actively explored for ultrasmall transistors beyond graphene. The current prevailing methods for producing MoS2 devices involve multiple wet chemistry steps, which not only are time consuming, but may also unfavorably affect material quality and impair device performance through the chemical processes. Here, the authors report the first dry-transferred pristine MoS2 field-effect transistors (FETs) without any post-transfer lithographical and chemical processes, by using a facile, completely dry transfer technique with high throughput and high precision in alignment. The authors also show that the device performance can be greatly boosted by thermal annealing. Combining the dry-transfer technique with thermal annealing, the authors achieve MoS2 FETs with mobility up to 76 cm2/(V s) and on/off ratios exceeding 107. The authors further show how continued annealing cycles improve the MoS2 devices' conductance, mobility, on/off ratio, transconductance, threshold voltage, and contact quality.